Adsorption behavior of herbicide paraquat from aqueous solutions using starfish particles: kinetic, isotherm, and thermodynamic studies. Issue 3 (27th March 2015) - Hao, Han; Feng, Jianguo; Chen, Weitao; Xiang, Sheng; Liu, Wenjun; Wu, Xuemin
Abstract The adsorption of paraquat (PQ) on starfish particles was investigated to calculate the kinetic, isotherm, and thermodynamic parameters. The experiments were carried out as a function of particle size of adsorbent, adsorbent dosage, contact time, initial PQ concentration, stirring speed, and temperature. The kinetic data followed the pseudo‐second‐order kinetic model, and the equilibrium data were well fitted by the Langmuir isotherm model with the maximum adsorption amount of 10.235 mg g−1 at 288 K. Thermodynamic parameters, including standard Gibbs free energy changes (ΔG0), standard entropy changes (ΔS0), and standard enthalpy changes (ΔH0) were also calculated. The results demonstrated that PQ was adsorbed onto starfish particles spontaneously and exothermically in nature. The adsorption process followed a physisorption mechanism. In addition, the starfish particles were successfully utilized to real sample. Hence, starfish particles are eligible for treating the wastewater containing PQ as an effective and low‐cost adsorbent. © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.